The relevance of outcome expectations in group hypnosis for stress reduction: a secondary analysis of a multicenter randomized controlled trial - Siewert, Julia; Teut, Michael; Brinkhaus, Benno; Fisch, Silvia; Kummer, Sonja (Frontiers in Psychology, 2024)
Background There is evidence that patients’ positive outcome expectations prior to study interventions are associated with better treatment outcomes. Nevertheless, to date, only few studies have investigated whether individual outcome expectations affect treatment outcomes in hypnosis. Objective To examine whether outcome expectations to hypnosis prior to starting treatment were able to predict perceived stress, as measured on a visual analog scale (VAS), after 5 weeks. Methods We performed a secondary data analysis of a multicenter randomized controlled trial of intervention group participants only. Study participants with stress symptoms were randomized to 5 weekly sessions of a group hypnosis program for stress reduction and improved stress coping, plus 5 hypnosis audio recordings for further individual practice at home, as well as an educational booklet on coping with stress. Perceived stress for the following week was measured at baseline and after 5 weeks using a visual analog scale (0–100 mm; VAS). Hypnosis outcome expectations were assessed at baseline only with the Expectations for Treatment Scale (ETS). Unadjusted and adjusted linear regressions were performed to examine the association between baseline expectations and perceived stress at 5 weeks. Results Data from 47 participants (M = 45.02, SD = 13.40 years; 85.1% female) were analyzed. Unadjusted (B = 0.326, t = 0.239, p = 0.812, R2 = 0.001) and adjusted (B = 0.639, t = 0.470, p = 0.641, R2 = 0.168) linear regressions found that outcome expectations to hypnosis were not associated with a change in perceived stress between baseline and after 5 weeks in the intervention group. Conclusion Our findings suggest that the beneficial effect of group hypnosis in distressed participants were not associated with outcome expectations. Other mechanisms of action may be more important for the effect of hypnosis, which should be explored in future research. Clinical trial registration: ClinicalTrials.gov, identifier NCT03525093.